Assessment of diabetic patient waiting time in a primary healthcare clinic - Shalihin, Mohd Shaiful Ehsan; Osman, Iskandar Firzada; Din, Muhammad Hapizie (Kulliyyah of Medicine, International Islamic University Malaysia, 2020)
Introduction: Long waiting time is a common issue complained by diabetic patients that came for an early morning appointment in a health clinic. Therefore, an audit was conducted among diabetic patients in a primary care clinic with the aim to assess the patients’ waiting time and to formulate strategies for improvement. Methods: This audit was conducted for four weeks using a universal sampling method in November 2017. All diabetic patients who attended the clinic during this period were included except those who required longer period such as critically ill patients or those who came for repeat medication or procedures. The arrival and departure time for each station was captured using the modified waiting time slip, which is manually filled at every station. The waiting and consultation time for registration, screening, laboratory investigation, diabetic educator, doctor and pharmacy were recorded. The data were entered into the statistical software SPSS version 17 for analysis. Results: Results showed that all patients were registered within 11.0 minutes (SD=2.52min). Average total waiting time to see a diabetic educator and a doctor was 20.9 minutes (SD=15.53min) and 33.23 minutes (SD=27.85min), respectively. Average waiting time for other stations was less than 10 minutes. Average total time spend in the clinic for a diabetic patient was 107.58 minutes, which is comparable to a non-diabetic patient. The identified problems were due to the poor tracing and filing system. Conclusion: Improvement strategies recommended include enforcing early file tracing prior to appointment and providing a checklist for consultation by doctors and diabetic educators.